Sistem Informasi Absensi Dan Pencatatan Kegiatan Harian Mahasiswa Magang Berbasis Website - Hartono, Rahmat (Journal of Information Systems and Business Technology, 2025)
The manual system for recording internship attendance and daily activities often leads to several issues, including data inaccuracies, inconsistent entries, and delays in reporting. These problems not only affect students but also make it difficult for supervisors to monitor and evaluate their performance effectively. To address these challenges, a web-based information system was developed to streamline the process of tracking student attendance and documenting daily internship activities in a more efficient, structured, and integrated manner. The system was developed using the Waterfall model, which consists of several phases: requirements analysis, system design, program implementation, functional testing, and system maintenance. It utilizes the PHP programming language, features a Bootstrap-based user interface, and employs MySQL as the database management system, all running on the XAMPP platform. Key features of the system include multi-user login access (for students, supervisors, and admins), daily attendance logging, student activity reporting, and automatic generation of weekly and monthly summaries in downloadable document format. Testing was conducted using the Black Box method, and the results confirmed that all system functionalities operate as intended and align with user expectations. This system is expected to serve as a digital solution for managing internship administration more effectively and fostering student discipline and accountability throughout the internship period.